LATE ABDOMINAL AORTIC ANEURISMATIC SAC RETRACTION AFTER EVAR - Viseu dos Santos, André Filipe (2018)
Introdution: In the last years, EVAR has been increasingly affirmed as the main surgical option for AAA correction without rupture. This procedure presents specific clinical and anatomical indications although it does not prevent the appearance of long-term complications associated with EVAR. Materials and Methods: A retrospective study of all patients submitted to EVAR was performed at the Hospital under study, between 01/01/2010 and 12/31/2016. After selection of 52 patients, applied the exclusion criteria, a total of 26 patients were obtained. This sample was Statistic analysed in order to evaluate the existence of any factor that relates or allows predicting aneurysmal retraction after an EVAR. Results: Correlation tests were performed, where only the variable Smoking History showed Statistic significance (Pearson r=-,390; p=0.049). This change was later verified with a comparison of means where it was verified that there was a significant difference between the groups with history of smoking (the one with the greatest retraction) and the group without smoking history. The influence of this variable on the retraction was verified through the Linear Regression analysis, in which statistical significance was verified (p = 0.032, B = −6.538), confirming the influence on the retraction. In a linear regression analysis for the remaining variables, although there was no significant difference, the variable largest diameter of the neck was the one that presented the greatest influence on the retraction, with B = 8.047 and p value closer to significance (p = 0.058). In the Binary Regression only the variable % thrombus in the neck presented significance outside the equation, showing no statistical significance (p = 0.071; Exp (B) = 0,121) in the equation. Conclusion: In summary, this study allows us to infer that the performance of EVAR in patients with AAA presents better results when patients have a personal history of smoking. In addition, there is a tendency for the existence of a relation between the variable % thrombus in the cervix with the AAA retraction after EVAR.